2016
DOI: 10.1080/09670262.2016.1147085
|View full text |Cite
|
Sign up to set email alerts
|

Species differentiation in the genus Chara (Charophyceae): considerable phenotypic plasticity occurs within homogenous genetic groups

Abstract: Charophytes are benthic algae with a complex morphology and high phenotypic plasticity. This has led to ambiguities in species delineation. However, until now genetic studies on Chara have been based on samples collected from a restricted geographic range or only included a restricted number of taxa. This may have hindered a general interpretation of the results. We applied barcoding of matK, a rapidly evolving coding section of the plastid genome, in 324 Chara samples collected from 19 countries, in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 49 publications
(70 reference statements)
1
18
0
1
Order By: Relevance
“…Wood & Imahori (1965), na monografia mundial de Characeae, interpretaram que o gênero possuía poucas espécies com ampla gama de variações morfológicas e o subdividiram em subgêneros, seções e subseções, baseando-se em caracteres puramente morfológicos Borges & Necchi-Junior 2017;Urbaniak & Combik 2017). Esse arranjo embora ainda amplamente utilizado, tem sido questionado por trabalhos com enfoque molecular (Meiers et al 1999;Sakayama et al 2009;Schneider et al 2015;Schneider et al 2016;Nowak et al 2016;Borges & Necchi-Junior 2017).…”
Section: Introductionunclassified
“…Wood & Imahori (1965), na monografia mundial de Characeae, interpretaram que o gênero possuía poucas espécies com ampla gama de variações morfológicas e o subdividiram em subgêneros, seções e subseções, baseando-se em caracteres puramente morfológicos Borges & Necchi-Junior 2017;Urbaniak & Combik 2017). Esse arranjo embora ainda amplamente utilizado, tem sido questionado por trabalhos com enfoque molecular (Meiers et al 1999;Sakayama et al 2009;Schneider et al 2015;Schneider et al 2016;Nowak et al 2016;Borges & Necchi-Junior 2017).…”
Section: Introductionunclassified
“…Numerous morphological and molecular results such as AFLP or sequencing data indicate a very close relationship between species belonging to this section (Urbaniak 2011a;Urbaniak & combik 2013;Schneider et al 2015;Schneider et al 2016). The precise distinction between the tested species based on morphological features is possible using quantitative characteristics, rather than descriptive characteristics (kraUSe 1997; Urbaniak & combik 2013;Urbaniak & Gąmbka 2014).…”
Section: Molecular Phylogeny and Genetic Variations Among Species Of mentioning
confidence: 99%
“…By contrast, in the same way using combined morphological characteristics of the species and analysis of about 6214 bp, noWak et al (2016) coudl not separate Chara individuals and all of the studied species. This was also not possible by means of several barcode markers on a much larger data set (Schneider et al 2016) using amplified fragment length polymorphism (AFLP) analysis, which has been used to determine the taxonomy of the genus Chara (Urbaniak & combik 2013). Because of these difficulties, we performed this study focussing on four freshwater species (two diplostichous aulacanthous species (Chara hispida L. and C. rudis a.braUn) and two diplostichous thylacanthous species (C. intermedia a.braUn and C. polyacantha a.braUn) and one brackish water species (a diplostichous thylacanthous species, C. baltica brUzeLiUS, in transition to slightly isostichous), which belongs to the section Hartmania.…”
Section: Introductionmentioning
confidence: 99%
“…rays without cortex) is strongly influenced by growth conditions (Bazzichelli and Abdelahad 2009 and references therein). Moreover, recent genetic analysis suggested that C. gymnophylla should be divided into tylacanthous forms (which are closely related to Chara contraria A.Braun ex Kützing) and aulacanthous forms (which are related to C. vulgaris) (Schneider et al 2016). Nevertheless, C. gymnophylla is currently accepted as valid species (Guiry and Guiry 2019).…”
mentioning
confidence: 99%
“…Chara virgata (formerly Chara delicatula C.Agardh) is very similar to Chara globularis Thuiller, from which it is distinguished by the features of the stipulodes (well developed and rudimentary in the upper and lower row, respectively), of the spines (papillar), of the bractlets (longer than the oogonia) and for the isostic or tylacanthous cortex (Bazzichelli and Abdelahad 2009). Nevertheless, such morphological features (particularly the stipulodes) are often mixed in the two species, despite they recently resulted clearly genetically differentiated (Schneider et al 2016). The two species are also quite different in their ecology: C. virgata is considered as an indicator of oligotrophic waters, while C. globularis is considered as an indicator of eutrophic environments (Blindow 1992;Toivoneh and Huttunen 1995;Krause 1997), although mixed populations of the two species in the same water bodies are known from central Italy (Bazzichelli and Abdelahad 2009) and Poland (Pelechaty et al 2004).…”
mentioning
confidence: 99%